(untitled) (Medico Legal Update, 2019)
On one hand the horizon of human rights is expanding but at the same time the crime rate is also increasing. In this context, custodial deaths are among most contentious deaths for investigation by forensic experts. These deaths sometimes invite mass resentment and condemnation. Not that always such deaths are due to unnatural or violent causes; indeed most of the time they are due to natural causes. To analyse custodial deaths from all aspects present prospective study was undertaken. A total of 135 (119 male and 16 female) cases of custodial deaths were examined in detail over a study period of 2 years. Based on place of confinement 100 cases (74.07%) died in jail custody, 33 cases (24.45%) died in mental hospital custody and in 2 cases (1.48%) death occurred in police custody. Among 92 cases (out of 135) in which final cause of death was declared, the death was natural in 95.65% while in 4.35% it was unnatural. Pulmonary tuberculosis was the most common natural cause among prison custodial deaths (22.8%, n=16). In mental hospital custody coronary artery disease (12.8%, n=9) was the leading cause of natural death. As far as unnatural deaths are concerned, there were two cases each of suicidal and accidental deaths (2.17% each) and no case of homicidal death was noticed.